A randomized, double-blind, placebo-controlled trial of coenzyme Q10 in Huntington disease. (10th January 2017) - McGarry, Andrew; McDermott, Michael; Kieburtz, Karl; de Blieck, Elisabeth A.; Beal, Flint; Marder, Karen; Ross, Christopher; Shoulson, Ira; Gilbert, Peter; Mallonee, William M.; Guttman, Mark; Wojcieszek, Joanne; et al.
Abstract : Objective: To test the hypothesis that chronic treatment of early-stage Huntington disease (HD) with high-dose coenzyme Q10 (CoQ) will slow the progressive functional decline of HD. Methods: We performed a multicenter randomized, double-blind, placebo-controlled trial. Patients with early-stage HD (n = 609) were enrolled at 48 sites in the United States, Canada, and Australia from 2008 to 2012. Patients were randomized to receive either CoQ 2, 400 mg/d or matching placebo, then followed for 60 months. The primary outcome variable was the change from baseline to month 60 in Total Functional Capacity score (for patients who survived) combined with time to death (for patients who died) analyzed using a joint-rank analysis approach. Results: An interim analysis for futility revealed a conditional power of <5% for the primary analysis, prompting premature conclusion in July 2014. No statistically significant differences were seen between treatment groups for the primary or secondary outcome measures. CoQ was generally safe and well-tolerated throughout the study. Conclusions: These data do not justify use of CoQ as a treatment to slow functional decline in HD. ClinicalTrials.gov identifier: NCT00608881. Classification of evidence: This article provides Class I evidence that CoQ does not slow the progressive functional decline of patients with HD.